Visit‐to‐Visit Systolic Blood Pressure Variability Independently Predicts Cardiovascular Events in a Kidney Transplant Recipients' Cohort - Elisabetta Bussalino; Daniela Picciotto; Lucia Macciò; Angelica Parodi; Maria Teresa Gandolfo; Francesca Viazzi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The predictive role of blood pressure variability for all‐cause mortality and fatal and nonfatal cardiovascular events has been described in the general population and in patients with diabetes, independently of mean BP. Although systolic blood pressure variability has been proposed as an informative measure for predicting clinical outcomes in patients with chronic kidney disease, its role in kidney transplant recipients is still debatable. Methods and Results We performed a retrospective, observational, monocentric analysis of all kidney transplant recipients in follow‐up at the outpatient Nephrology Clinic of San Martino Hospital from January 1, 2016 to December 31, 2016, who underwent kidney transplantation >12 months. The primary outcome was a fatal or nonfatal cardiovascular event (myocardial infarction, unstable angina, stroke, and hospitalization for heart failure). Visit‐to‐visit systolic blood pressure variability was expressed as the SD of systolic blood pressure values recorded at baseline and 3 months up to 18 months. Among the 272 patients (mean age, 64±13; 63% men) included in the present analyses, for each increase of 2.7 mm Hg in systolic blood pressure SD, the risk for events increased 3‐fold (hazard ratio [HR], 3.1 [95% CI, 1.19–7.88]; P=0.02), and patients in the highest tertile of systolic blood pressure SD showed a 4‐fold increased risk (HR, 4.1 [95% CI, 1.34–12.43]; P=0.01). This relationship was maintained even after incremental adjustment for time‐averaged pulse pressure, age, diabetes, and prior cardiovascular event (HR, 3.2 [95% CI, 1.1–10.0]; P=0.04). Conclusions Long‐term blood pressure variability represents a risk factor for cardiovascular events in kidney transplant recipients, even independently by several confounding factors including blood pressure load.